2018
DOI: 10.3389/fphar.2018.00945
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Wound-Healing Properties of Medicinal Plants: The Case of Phyllanthus muellerianus

Abstract: Phyllanthus muellerianus (Family Euphorbiaceae) is a shrub, which is widely distributed in West Africa and employed traditionally as a wound-healing agent especially in Ghana. The aim of the study was to determine the in vivo wound-healing activity of aqueous aerial part extract of P. muellerianus (PLE) and its major isolate, geraniin. Excision and incision wound models were used to determine the wound-healing activity. Wounds were treated with PLE (0.25, 0.5, and 1% w/w) and geraniin (0.1, 0.2, and 0.4% w/w) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 45 publications
1
41
0
Order By: Relevance
“…It has been documented that the amount of hydroxyproline in wound tissue is widely used as a measure of collagen quality (Boakye et al, 2018). To validate our histological findings, hydroxyproline contents in the lesions were assessed, and the results revealed that hydroxyproline contents in the wound tissues of SPPE-treated rats were higher.…”
Section: Discussionmentioning
confidence: 51%
“…It has been documented that the amount of hydroxyproline in wound tissue is widely used as a measure of collagen quality (Boakye et al, 2018). To validate our histological findings, hydroxyproline contents in the lesions were assessed, and the results revealed that hydroxyproline contents in the wound tissues of SPPE-treated rats were higher.…”
Section: Discussionmentioning
confidence: 51%
“…Like many countries in Sub-Saharan Africa, Ghana hosts a number of plants with medicinal properties [25]. However, just a handful of studies have exploited the activity of these plants against wound infected bacterial pathogens [14,18]. For instance, Boakye et al [18] determined the in vivo wound-healing activity of aqueous aerial part extract of a medicinal plant using the case of only Phyllanthus muellerianus.…”
Section: Discussionmentioning
confidence: 99%
“…However, just a handful of studies have exploited the activity of these plants against wound infected bacterial pathogens [14,18]. For instance, Boakye et al [18] determined the in vivo wound-healing activity of aqueous aerial part extract of a medicinal plant using the case of only Phyllanthus muellerianus. Agyare et al [14] also evaluated the antimicrobial and wound healing potential of two plants; Justicia flava and Lannea welwitschii.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar test was done using 1% dimethyl sulfoxide (DMSO) solution (used as a negative control for this test), and the absorbance ( Ad ) was measured [ 19 , 20 ]. The IC 50 for CFHE was estimated.…”
Section: Methodsmentioning
confidence: 99%